2009
DOI: 10.5194/bgd-6-10137-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sargasso Sea phosphorus biogeochemistry: an important role for dissolved organic phosphorus (DOP)

Abstract: Abstract. Inorganic phosphorus (SRP) concentrations in the subtropical North Atlantic are some of the lowest in the global ocean and have been hypothesized to constrain primary production. Based upon data from several transect cruises in this region, it has been hypothesized that dissolved organic phosphorus (DOP) supports a significant fraction of primary production. In this study, a time-series of phosphorus biogeochemistry is presented for the Bermuda Atlantic Time-series Study site, including rates of phos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
153
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(161 citation statements)
references
References 66 publications
(45 reference statements)
7
153
0
Order By: Relevance
“…Despite its importance, DOP dynamics have been understudied. Seasonal variations in DOP concentration have been reported in coastal regions (Monaghan and Ruttenberg, 1999;Van Der Zee and Chou, 2005) and open subtropical regions (Karl and Tien, 1997;Lomas et al, 2010). We also reported multiyear DOP dynamics in Funka Bay, Hokkaido, Japan (Yoshimura and Kudo, 2011).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Despite its importance, DOP dynamics have been understudied. Seasonal variations in DOP concentration have been reported in coastal regions (Monaghan and Ruttenberg, 1999;Van Der Zee and Chou, 2005) and open subtropical regions (Karl and Tien, 1997;Lomas et al, 2010). We also reported multiyear DOP dynamics in Funka Bay, Hokkaido, Japan (Yoshimura and Kudo, 2011).…”
Section: Introductionmentioning
confidence: 58%
“…DOP dynamics have not been fully examined in the relatively productive subarctic regions compared with the comprehensive studies in subtropical oligotrophic regions such as stations ALOHA (Karl and Tien, 1997) and BATS (Lomas et al, 2010). In the Oyashio region, a western boundary current of the subarctic circulation in the North Pacific, phytoplankton growth is regulated by nitrate, silicic acid, and iron while a significant amount of soluble reactive P (SRP) remains throughout the year (Nakayama et al, 2010;Nishioka et al, 2007;Saito et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Based on model calculations, the input of DOP (locally equivalent to "new" P) is 12 mmol P m −2 year −1 , which is sufficient to support approximately 50% of P lost in sinking particulate matter (Roussenov et al, 2006). In a separate study, Lomas et al (2010) supported this hypothetical flux of DOP into the North Atlantic subtropical gyre via transport by subtropical mode water. Based on a comprehensive 5-year data set collected at the Bermuda Atlantic Time-series Site (BATS) that included multiple P pools and their dynamics, the authors concluded that imported DOP supports approximately 25% of annual primary production and essentially all of the P exported as sinking particles.…”
Section: Global Open Ocean Dopmentioning
confidence: 98%
“…Phosphorus appears to limit summer production, though iron may also play a role (Sterner et al, 2004). Recent measurements of dissolved organic phosphorus (DOP) show the presence of a seasonally highly dynamic pool , suggesting the possibility that DOP may be fueling production in Lake Superior as in the Sargasso Sea (Lomas et al, 2010). Nitrate limits production in many parts of the world ocean, but it is in constant excess in Lake Superior.…”
Section: Introductionmentioning
confidence: 98%